BIODEGRADASI LIMBAH OLI BEKAS OLEH Lycinibacillus sphaericus TCP C 2.1 - Basuki, Witono (Center for Environmental Technology - Agency for Assessment and Application of Technology, 2011)
Mikroorganism has capability to degrade used engine oil was isolated fromÃ‚Â soil sample contaminated with used engine oil. One of the selected strainÃ‚Â TCP C 2.1 was identified by 16s rDNA as Lycinibacillus sphaericus. TheÃ‚Â microorganism can use hydrocarbon in used engine oil as the sole carbonÃ‚Â source and energy, also it significantly degraded almost all hydrocarbonÃ‚Â compounds in used engine oil. With its ability the microorganism has potencyÃ‚Â to be used as a single microbe for bioremediation of soil polluted by engine oil.